Housing inadequacy in Brazil: a reflection on its concepts and indicators - Rosso, Rafaela Ferreira; Souza, Natallia Sanches e; Seabra, Jessica (National Journal of City Management, 2024)
Research related to Brazil's housing deficit and inadequate housing conditions has been conducted for nearly 30 years with the aim of revealing housing-related deficiencies. While many authors focus on the housing deficit, this research concentrates on housing inadequacy, an index that reveals deficiencies preventing a residence from providing a high quality of life to its occupants. Such quality is measured by the building itself, the infrastructure of its urban area, and the legal title of the residence. This article proposes a brief historical context, demonstrating that the housing issue is deeply rooted in the country's socioeconomic inequalities, which have been perpetuated over the years by insufficient policies and challenges faced in urban planning. Furthermore, significant milestones in the history of the Fundação João Pinheiro (João Pinheiro Foundation - FJP) and the Instituto Brasileiro de Geografia e Estatística (Brazilian Institute of Geography and Statistics - IBGE) related to the collection, organization, and dissemination of data on housing conditions in Brazil were identified, with both institutions being crucial in this regard. Therefore, the aim was to discuss the habitability of Brazilian households by presenting concepts, indicators, and data from the most recent FJP publication on housing inadequacy from 2019. These data were systematized and presented in graphs, allowing for visualization and analysis. In conclusion, it was determined that the data released by the FJP are essential for diagnosing the housing scenario, are directly related to the literature review conducted, and provide crucial data for public policy formulation.
Keywords: Habitability; Inadequacy; FJP; PNADc